581 The Role of Biomarkers in Elite Sports (Balneo and PRM Research Journal, 2024)
Abstract: Biomarkers have emerged as valuable tools in the realm of elite sports, providing objective measures of athletes' physiological responses and potential for performance optimization. This article review delves into the significance and implications of biomarkers in elite sports, emphasizing their crucial role in supporting athletes' training, recovery, and overall success. The integration of biomarkers offers unprecedented opportunities for evidence-based decisions, personalized strategies, and injury prevention, revolutionizing the landscape of elite sports. Through comprehensive literature review and analysis, this article highlights the tremendous promise of biomarkers in optimizing athletic performance while also addressing the ethical considerations surrounding their implementation. As research continues to advance, biomarkers are poised to reshape the future of elite sports, enhancing performance and paving the way for the next generation of sporting legends.